Poor written pragmatic skills are associated with internalising symptoms in childhood: evidence from a UK birth cohort study - Ahmed, Kalim; Flouri, Eirini; Vigliocco, Gabriella (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction This study examined the relation between pragmatic language and internalising (depressive and anxiety) symptoms in 11-year-olds, using data from the 1958 British birth cohort study. Methods The cohort children were asked at age 11 to write an essay on their life as they imagined it would be at age 25. We analysed 200 of these essays for relevance, organisation and context-dependent references. Results We found associations between these aspects of pragmatic language and children's internalising symptom scores across parent and teacher ratings, even after adjustment for cognitive ability, socioeconomic position and structural language. Most notably, children writing more coherent essays had fewer teacher-rated internalising symptoms, after adjustment for confounders. Additionally, children who provided more relevant and varied information about their imagined future home-lives had fewer parent-rated internalising symptoms, after adjustment for confounders. Discussion The unique associations between pragmatic language skills and internalising symptoms observed are notable but preliminary, highlighting both the need for further research and potential applications for risk-assessment tools.